RATES OF REAL INVESTMENT EFFICIENCY: EVOLUTION AND DIFFICULTIES OF USE - Svetlana P. Ivanova; Alexey N. Litvinov (Вестник Российского экономического университета имени Г. В. Плеханова, 2017)
The article investigates rates of investment efficiency and points to problems arising while comparing investment projects, which are different in scale and duration. The authors discuss issues connected with shaping the system of rates to assess economic efficiency of real investment and offer recommendations aimed at modernizing the present methods of investment analysis. The authors put forward the rates to analyze investment efficiency by using methods of discounting which allow us to compare projects with different investment volumes, periods of functioning and return standards. These rates of efficiency must be used jointly to rank several investment projects.